2022
DOI: 10.2147/idr.s349566
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characterization of Extended Spectrum β-Lactamase and Carbapenemase-Producing Enterobacteriaceae Isolates from Bloodstream Infection Suspected Patients in Addis Ababa, Ethiopia

Abstract: Background Production of Extended spectrum beta-lactamase (ESBL) and Carbapenemase is the most common strategy for drug resistance in clinical isolates of Enterobacteriaceae . This study was conducted to determine the magnitude of ESBL and Carbapenemase production (CPE) among clinical isolates of Enterobacteriaceae causing bloodstream infections (BSI) in Ethiopia. Methods A cross-sectional study was performed from Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
(80 reference statements)
1
10
2
Order By: Relevance
“…On the other hand, Jamshidi et al in Iran showed that 90.4% of K. pneumoniae strains were ESBL producers, and bla TEM , bla SHV , and bla CTX−M genes were detected in 80.9%, 90.5%, and 76.2% of isolates, respectively, which was higher than our ndings [28]. The possible cause for this wide variation in the prevalence of ESBL could be attributable to differences in the geographical area of the research, overuse of broad-spectrum antibiotics, variation in antibiotic prescribing patterns, and a high rate of gastrointestinal tract colonization by ESBL-producing strains in the study site [6,29].…”
Section: Discussioncontrasting
confidence: 62%
“…On the other hand, Jamshidi et al in Iran showed that 90.4% of K. pneumoniae strains were ESBL producers, and bla TEM , bla SHV , and bla CTX−M genes were detected in 80.9%, 90.5%, and 76.2% of isolates, respectively, which was higher than our ndings [28]. The possible cause for this wide variation in the prevalence of ESBL could be attributable to differences in the geographical area of the research, overuse of broad-spectrum antibiotics, variation in antibiotic prescribing patterns, and a high rate of gastrointestinal tract colonization by ESBL-producing strains in the study site [6,29].…”
Section: Discussioncontrasting
confidence: 62%
“…In previous studies conducted in Ethiopia, the rate of carbapenem resistance among Gram-negative rods was low ranging 1.7–15.1% ( Misha et al, 2021 ; Tekele et al, 2021 ; Seman et al, 2022 ; Tilahun et al, 2022 ; Alemayehu et al, 2023 ). However, our findings showed an increase in resistance to carbapenems (18.6%).…”
Section: Discussionmentioning
confidence: 91%
“…Back then, it could only be detected in some isolates of Acinetobacter baumannii , with no evidence of its presence in other isolates. However, NDM is no longer limited to Acinetobacter species and has been found in various GNB, such as K. pneumoniae , K. variicola , E. coli , P. aeruginosa , and P. mendocina ( Legese et al, 2022 ; Seman et al, 2022 ; Sewunet et al, 2022 ; Tufa et al, 2022 ). This enzyme is particularly concerning because it can rapidly spread between different bacterial species through horizontal gene transfer, leading to the emergence of extensively drug-resistant infections ( Da Silva and Domingues, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has chromosomal mediated gene bla SHV which is responsible for intrinsic resistance, whereas, in the case of acquired resistance, K. pneumoniae use to produce extended-spectrum -lactamase (ESBLs) and carbapenemases that are associated with the resistance to different generations of cephalosporins and carbapenems. 6 , 7 Moreover, K. pneumoniae displayed resistance against colistin due to the presence of plasmid-mediated mobilized colistin resistance ( mcr ) genes. 8 Due to the emergence of resistant variants and a dearth of new antibiotics, treatment options for MDR K. pneumoniae are limited.…”
Section: Introductionmentioning
confidence: 99%